Charting Future Growth for Islamic Finance Talents in Malaysia: A Bibliometric Analysis on the Islamic Finance Domains and Future Research Gaps - Abd. Wahab, Norazlina; Mohd Yusof, Rosylin; Zainuddin, Zaemah; Nizam Shamsuddin, Jamaltul; Mohamad, Siti Farah Norbaini (Emerald Group Publishing Limited, 2023)
This paper aims to provide an overview of research topics and publications produced by Islamic Finance scholars in Malaysia, focusing on six research domains (Shariah-based, Islamic Finance, Islamic Economics, Islamic Accounting, Islamic Management and Halal Management) in 5 public universities in Malaysia. Design/ Methodology Approach: This study seeks to analyse the research gaps and recommend future research based on publications produced by Islamic Finance scholars from five public universities in Malaysia. Data on talents were collected from the MIFER report 2016 and each universities’ website, while research and publications of the talents were collected from Google Scholar and the Scopus database. The extracted data were analysed using bibliometric analysis in VOSviewer version 1.6.15. Findings: The results show that the five selected universities talents have different research strengths according to six research domains highlighted in MIFER 2021 and Beyond Report. All five universities are found to contribute the least research in Halal Management domain. In view of the increasing prominence of this area of research in the national and international levels, these universities and other universities in Malaysia can generate more research in Halal Economy, Halal Management, and other related areas within this domain. Our finding indicated that each university tends to have a strength according to the different domains, and 2019 is the most productive year for Islamic Finance publications. Analysis from productive scholars and co-citations shows that the authors collaborate within the same university to create a different topic for each research cluster. Research Limitation/ Implications: The bibliometric analysis only captures the general keyword terms, which may be limited to the only generalised sub-research areas. Practical Implications: This bibliometric study, which is based on the expertise of researchers’, complements meta-analysis and qualitative structured literature reviews aids researchers or talents in developing future research directions such as Green economy, Cryptocurrency, Fintech, Halal Management and others. In addition, this is a case study in nature and can serve to enhance understanding the landscape o Islamic finance education and as a reference for practices in institutions of higher learning from around the world. Originality/Value: To the best of the authors’ knowledge, this study is a new research initiative comparing five top program providers in the field of Islamic finance using a bibliometric approach to enhance talent development and capacity building. With the government’s efforts to further promote Malaysia as the Islamic Financial Hub, this article highlights the research gap in Islamic finance based on scholars’ publications from selected 5 Malaysian universities and potential topics for future research. This article focuses on the research domain for each university, the trend of publishing, the number of journals published by academics, productive scholars, and citations by Malaysian universities, and examines if the publications align with current industry needs